STRENGTHENING POSITIVE WORK ATTITUDES OF PERSONS WITH DISABILITIES THROUGH ORGANIZATIONAL JUSTICE, CULTURAL SENSITIVITY, AND INFORMATION TRANSPARENCY IN THE CONTEXT OF STIGMA PERCEPTION - Br Simamora, Rusdiana; Novranda Surbakti, Michael (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines how organizational justice, cultural sensitivity, and information transparency influence the positive work attitudes of persons with disabilities, with stigma perception incorporated as a moderating variable. The research aims to deepen the understanding of how organizational and social dynamics interact in shaping inclusive employment practices. Using quantitative explanatory design, the study employs covariance-based Structural Equation Modeling (SEM). Data were obtained from 100 respondents with physical disabilities working in micro, small, and medium enterprises (MSMEs), private companies, social service organizations, government institutions, and educational settings across Medan, Binjai, and Langkat. A five-point Likert scale questionnaire was administered, and the data were analyzed in R Studio using the lavaan, semPlot, and psych packages. Instrument validity and reliability were assessed through CFA, AVE, CR, and HTMT, while model fit was evaluated using CFI, TLI, RMSEA, and SRMR. The findings reveal that organizational justice (β = 0.62, p < 0.01), cultural sensitivity (β = 0.48, p < 0.05), and information transparency (β = 0.55, p < 0.01) each have a significant positive effect on positive work attitudes. The moderation analysis shows that stigma perception weakens the influence of organizational justice and cultural sensitivity yet strengthens the effect of information transparency. Descriptive results further indicate that although stigma remains a substantial barrier, respondents still demonstrate generally high levels of positive work attitudes.